A Review of the Phytochemistry and Pharmacology of Phyllanthus urinaria L. - Geethangili, Madamanchi; Ding, Shih-Torng (Frontiers in Pharmacology, 2018)
The genus Phyllanthus was a famous plethora of important biological functions, and a member of a diverse family of plants known as Euphorbiaceae. Phyllanthus urinaria (Linnaeus) was an annual perennial herbal species found in tropical Asia, America, China and the Indian Ocean islands. P. urinaria is utilized in folk medicine as a cure to treat jaundice, diabetes, malaria, and liver diseases. Phytochemical investigations revealed that the plant is a rich source of secondary metabolites including lignans, tannins, flavonoids, phenolics, terpenoids and other secondary metabolities. Pharmacological activities include anticancer, hepatoprotective, antidiabetic, antimicrobial, and cardioprotective effects. Thus, for the first time, this present review summarizes the phytochemical constituents and their biological activities, biological studies on various crude extracts, fractions both in vitro and in vivo, and clinical trial information about P. urinaria. This review compiles 93 naturally occurring compounds from P. urinaria along with their structures and pharmacological activities. The review is expected to stimulate further research on P. urinaria, and its pharmacological potential for novel therapeutic agents.